Difficult Asthma - Heaney, Liam G.; Menzies-Gow, Andrew (India : Jaypee Brothers Medical Publishers, 2013)
Most patients with asthma are easily diagnosed and treated with the use of an inhaler or medication. Approximately five per cent of people that suffer from asthma have difficult or refractory asthma, whereby they experience persistent problems that are not controlled by standard treatment methods. Part of the Clinical Focus Series, this book provides a complete overview of difficult asthma, discussing the clinical assessment and management of this complex condition. Beginning with the epidemiology and characteristics of severe asthma, the book defines current understanding of the immunological mechanisms and disease heterogeneity. It also offers insight into how the condition can affect the physical and psychological aspects of a person s life. Separate chapters examine novel therapeutic strategies and the economic burden of refractory asthma.
1. Definition, Epidemiology, and Phenotypes of Severe Asthma Sally E Wenzel 2. Economic Burden of Difficult Asthma 14 Ciaran O'Neill, Claire Telford 3. Clinical Assessment of Difficult Asthma 24 Annemarie Sykes, Andrew Menzies-Gow 4. Adherence in Difficult Asthma 40 Rob Horne, Liam G Heaney 5. Psychological Morbidity in Difficult-to-treat Asthma 56 Adel H Mansur, Alison Pooler 6. Difficult Asthma in Children 73 Surendran Thavagnanam, Michael D Shields 7. Difficult Asthma-The Patient's Perspective 92 Jennifer M Versnel, Liam G Heaney 8. Comorbidity in Refractory Asthma 102 Robert Niven 9. Molecular and Immunological Basis for Severe Therapy-resistant Asthma 120 Ian M Adcock, Kian F Chung 10. Monitoring and Natural History of Refractory Asthma 145 Christopher Brightling 11. Novel Treatment Strategies in Refractory Asthma 163 Neil C Thomson, Rekha Cha
Incluye contenido
Incluye índice
Incluye bibliografía
Keywords: ASMA